Model Design of the Infrastructure Layer of Postal System - Lucia Madlenakova; Radovan Madlenak; Anna Rudawska (Communications - Scientific letters of the University of Zilina, 2016)
The idea and purpose of this article reside in addressing the postal system model by decomposing into independent subsystems in the form of displaying through a layered network model. Postal service is generally seen as a sequence of processes for collecting and distributing shipments for the purpose of their delivery. This service can also be defined as service guaranteeing functions in identified layers of the postal system. This allows to identify the functions and protocols for mutual communication and interoperability between different postal systems including solutions of issues of regulation.